Tribological behavior of surface treated H13 steel (Superficies y Vacío, 2013)
The microstructure of CrN/AlN films, prepared by reactive magnetron sputtering was analysed and related to the friction and wear behaviour of the films on H13 tool steel. The films were prepared by conventional reactive magnetron sputtering and Ar + N2 conventional gas mixture but also a second set adding an extra amount of reactive gas to the initial mixture and finally, adding an extra source of nitrogen near the substrate during sputtering. The samples were analysed by scanning electron microscopy + energy dispersive microanalysis, and X-ray diffraction. The results of the microstructural analysis revealed a clear difference in the morphology growth of the films when extra nitrogen was used compared to the conventionally prepared films. The most effective method to produce AlN was to introduce extra nitrogen. Pin-on-disk wear experiments were carried out under dry conditions and in ambient air, to investigate the tribological behaviour. The results revealed that tribological properties of the layers improved somewhat unlike those of the untreated H13 steel.